2022
DOI: 10.1007/s41669-022-00342-6
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Surgical Care at Public Sector District Hospitals in India: Implications for Universal Health Coverage and Publicly Financed Health Insurance Schemes

Abstract: Background In low- and middle-income countries (LMICs), provisioning for surgical care is a public health priority. Ayushman Bharat Pradhan Mantri-Jan Aarogya Yojana (AB PM-JAY) is India’s largest national insurance scheme providing free surgical and medical care. In this paper, we present the costs of surgical health benefit packages (HBPs) for secondary care in public district hospitals. Methods The costs were estimated using mixed (top-down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…Prinja et al reported the cost per institutional delivery as USD 62.9 (95% CI 43.8-95.8) which was lower than that of the present study, maybe because they calculated it for the secondary level of healthcare [17]. Singh et al reported the mean cost for vaginal delivery and caesarean delivery as USD 149 (min-max: 53 to753) and USD 226 (min-max: 79-529), respectively, which were higher than that observed in the present study, maybe because they included the cost of postnatal stays in their calculations, whereas, in the present study, postnatal costs were not included and the focus remained exclusively on intranatal services [18]. Under health insurance schemes such as the Chiranjeevi Yojana [10] and the Ayushman Bharat Pradhan Mantri-Jan Aarogya Yojana (AB PM-JAY) [8,9], the Rajasthan government pays INR 11,500 (USD 153.4) and INR 14,100 (USD 188.1) per caesarean delivery, respectively.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Prinja et al reported the cost per institutional delivery as USD 62.9 (95% CI 43.8-95.8) which was lower than that of the present study, maybe because they calculated it for the secondary level of healthcare [17]. Singh et al reported the mean cost for vaginal delivery and caesarean delivery as USD 149 (min-max: 53 to753) and USD 226 (min-max: 79-529), respectively, which were higher than that observed in the present study, maybe because they included the cost of postnatal stays in their calculations, whereas, in the present study, postnatal costs were not included and the focus remained exclusively on intranatal services [18]. Under health insurance schemes such as the Chiranjeevi Yojana [10] and the Ayushman Bharat Pradhan Mantri-Jan Aarogya Yojana (AB PM-JAY) [8,9], the Rajasthan government pays INR 11,500 (USD 153.4) and INR 14,100 (USD 188.1) per caesarean delivery, respectively.…”
Section: Discussioncontrasting
confidence: 79%
“…were collected from the hospital administration department. A predesigned, pre-tested, semi-structured pro-forma that has already been used in previous Indian studies [17,18] was used to collect the relevant data after modifying it for intranatal services. Data on the average life of the equipment were collected by interviewing staff members working with that equipment.…”
Section: Figure 1: Sampling Technique and Study Designmentioning
confidence: 99%
“…The reimbursement rate under PM-JAY comprises the hospitalisation cost, the procedure cost, pre-admission consultation and diagnostic work-up, as well as the cost of 15-days of medication following discharge. We analysed the CHSI phase I dataset which has shown that on average across all surgical packages of care, 60% of the total cost is derived from the procedure alone 6 27. As a result, we focused on the inpatient and procedure cost centres to determine weights of medical and surgical packages, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have reported the high economic burden of NCDs in terms of out-of-pocket expenditure (OOPE) and catastrophic health expenditure for those utilising care from private sector providers [19][20][21][22]. Multiple studies conducted in different states of India have reported the input costs incurred by public facilities [23][24][25][26][27][28][29][30]. There is a very small set of studies reporting on the costs in the private sector but none of these studies have focused on NCD care [23,30].…”
Section: Introductionmentioning
confidence: 99%